Towards the construction of the Mu2e electromagnetic calorimeter at Fermilab. Issue 1 (1st November 2022) - Atanov, N.; Baranov, V.; Borrel, L.; Bloise, C.; Budagov, J.; Ceravolo, S.; Cervelli, F.; Colao, F.; Cordelli, M.; Corradi, G.; Davydov, Y. I.; Di Falco, S.; et al.
Abstract : Mu2e will search for the Charge Lepton Flavor Violating (CLFV) conversion of a muon into an electron in the field of a nucleus. A clean discovery signature is provided by the mono-energetic conversion electron ( Ee = 104.96 MeV). If no events are observed, Mu2e will set a limit on the ratio between the conversion and the nuclear capture rate below 3 × 10 −17 (at 90% C.L.). In order to confirm that the observed candidate is an electron, the calorimeter resolution requirements are to provide Eres < 10%, Tres < 500 ps for 100 MeV electrons while working in vacuum and in a high radiation environment and high magnetic field. The calorimeter is made of two annular aluminum disks, each one filled with 674 pure CsI crystals read out by SiPMs. A sophisticated mechanics and cooling system has been developed to support the crystals and cool the sensors. Radiation hard analog and fast digital electronics have been developed. In this paper the QC tests performed on the produced components and the construction status are reported, as well as the results obtained on the large size prototype with test beam data and at a cosmic ray test stand.